Tracking Reaction Pathways by a Modular Flow Reactor Coupled to Electrospray Ionization Mass Spectrometry. Issue 10 (27th September 2021) - Tripodi, Guilherme L.; Derks, Max T. G. M.; Rutjes, Floris P. J. T.; Roithová, Jana
Abstract: Invited for this month's cover is the group of Jana Roithová at the Radboud University (The Netherlands). The cover picture shows a mini‐plant for automated monitoring of chemical reactions. Flow chemistry enables screening of chemical reactions under well‐defined conditions that can  systematically vary. Mass spectrometry couples it with the detection of low abundant reaction intermediates. Therefore, this platform allows tracking reaction pathways, monitoring reaction kinetics of intermediates and is set for a discovery of novel chemical transformations in future. Read the full text of their Full Paper at 10.1002/cmtd.202100046 . Abstract : "… The biggest challenge was to figure out how to work with the flow reactors to be able to monitor the reaction kinetics with ESI‐MS detection… " Find out more about the story behind the front cover research at 10.1002/cmtd.202100046 .